Biofortification of Hard Red Winter Wheat by Genes Conditioning Low Phytate and High Grain Protein Concentration. Issue 5 (26th July 2018) - Venegas, Jorge P.; Graybosch, Robert A.; Wienhold, Brian; Rose, Devin J.; Waters, Brian M.; Baenziger, P. Stephen; Eskridge, Kent; Bai, Guihua; Amand, Paul St.
Abstract : Recombinant inbred lines (RILs) of winter wheat ( Triticum aestivum L.) were used to determine whether the combination of low grain phytate (LPA) conditioned by lpa1‐1 and Gpc‐B1 (where GPC stands for grain protein content) alleles would simultaneously increase beneficial mineral concentrations and grain protein without pleiotropic effects on grain yield. Four different genotypes (LPA‐GPC, LPA‐wild type [WT], WT‐GPC, or WT‐WT) were used as treatments in field experiments in Nebraska. Genotypic effects on senescence, grain yield, grain volume weight, grain protein, Fe, Zn, and other mineral grain concentrations were determined. Low grain phytate alone and in combination with GPC increased dialyzed Zn, Ca, and Mn. Gpc‐B1 had a slight effect on grain protein concentration in the tested genetic backgrounds and environments. The combination of LPA and GPC did not lower grain yield, grain protein, or total grain Fe and Zn concentrations. However, the LPA‐GPC combination significantly reduced grain volume weight. The LPA allele alone reduced grain protein concentration. Introgression of lpa1‐1 alleles into adapted Great Plains winter wheat materials can improve dialyzed Zn, Ca, and Mn concentrations without reducing grain yield and, coupled with introgression of Gpc‐B1, provide more nutritious wheat kernels.